Methodological basis for the definition of market and cadastral value of land plots of settlements - A. D. Vlasov (Статистика и экономика, 2018)
Purpose of research. Determine the investment income of the entrepreneur for the land. To substantiate the market value of the  developed land plot with the operating business for tax purposes.Materials and methods. The basis of the paper is the norms of thelaw in appraisal activity; the results of cadastral evaluation of real estate objects in Russian settlements; the method of  comparative analysis of factors determining the market and  cadastral value of real estate objects.Results. Methodological bases of calculation of market and cadastralvalue of built-up land plots of settlements as capitalized rent of non- reproducible factors of market value of a single real estate object are formulated. It is shown that in the theory and practice of  measurement of market and cadastral value of the built-up parcels  of land of settlements of Russia article 3 of the law 135-Federal Law  of 29.07.1998 is violated, in consequence of what, the market and  cadastral value of capital construction in 2–5 times is overestimated,  and the market and cadastral value of parcels of  land in 2–10 times is underestimated. The formula of calculation of  investment profit of the entrepreneur for the land plot is offered.Conclusion. Regardless of the method (technology) of property valuation, cadastral value of built-up land in a settlement should be determined as the difference between the market value of a  single property and the market value of its improvements, using the  built-up land as analogs. That is, excluding from the value of a single property the value of improvements of the land, we receive the  market value of the built-up land, as “not built-up” clause 20,  Federal Valuation Standard №7.